Acceleration parameters for polycarbonate under blue LED photo-thermal aging conditions. (June 2019) - Gandhi, Kaushal; Hein, Christopher L.; van Heerbeek, Rieko; Pickett, James E.
Abstract: Acceleration parameters have been determined for bisphenol A polycarbonate (PC) exposed to blue light emitting diodes (LED) in a commercial apparatus for testing optical components using absorbance at 360 nm as a proxy for yellowing. The effect of temperature in the range of 90–120 °C gave linear Arrhenius plots with activation energies of 30–48 kJ/mol, depending on the presence of stabilizers. Experiments at irradiances of 5–75 kW/m 2 showed good reciprocity with the rate of degradation extrapolating to zero at zero irradiance. Parallel experiments using xenon arc irradiation with UV filters showed that the yellowing was proportional to the sample thickness up to at least 6 mm. The activation energies and thickness dependence are much different from the findings for PC outdoor weathering. Examples are shown for making service life predictions using these acceleration parameters. Highlights: Polycarbonate exposed to blue LED light undergoes yellowing. The activation energy is 30–48 kJ/mol, depending on stabilization. The yellowing obeys reciprocity and shows no thermal component to the yellowing. The yellowing goes through the thickness of the part up to at least 6 mm.